Petrochronology of the Terre Adélie Craton (East Antarctica) evidences a long-lasting Proterozoic (1.7–1.5 Ga) tectono-metamorphic evolution — Insights for the connections with the Gawler Craton and Laurentia - Naumenko-Dèzes, M.O.; Rolland, Y.; Lamarque, G.; Duclaux, Guillaume; Gallet, S.; Bascou, J.; Ménot, R.P. (Gondwana Research, 2020)
International audience The Terre Adélie Craton displays superimposed strain fields related to the Neoarchean (2.6–2.4 Ga, M1) and Paleo-Mesoproterozoic (1.7–1.5 Ga, M2) metamorphic events. M1 is a regional granulite facies event, constrained by P-T modelling at ~0.8–1.0 GPa – 800–850 °C, followed by a decompressional retrogression in the upper amphibolite facies at ~0.6 GPa – 750 °C. M2 Stage 1 P-T peak is constrained at 0.6–0.7 GPa – 670–700 °C, followed by a steep P-T path down to 0.3 GPa – 550 °C. Retrogression after M2 PT peak occurred in a context of dextral shearing along the Mertz Shear Zone along with thrust motions within the eastern Terre Adélie Craton. In this paper, we present a series of 63 new 40Ar/39Ar ages of biotite and amphibole pairs in mafic rocks from a complete traverse of the Terre Adélie Craton. 40Ar/39Ar dating constrains M2 amphibolite facies metamorphism at a regional scale between 1700 and 1650 Ma, during stage 1 peak metamorphism. During retrogression, lower amphibolite facies recrystallization mainly occurred along vertical shear zones and mafic dykes between 1650 and 1600 Ma (Stage 2), followed by amphibolite to greenschist facies metamorphism until after 1500 Ma (Stage 3). At the scale of the Mawson continent, this event is related to the growth of an active margin above an oblique subduction zone. The supra-subduction model best explains opening of Dumont D'Urville and Hunter basins at 1.71 Ga followed by their rapid closure and metamorphism at 1.70 Ga. In this context, episodic shear zone reactivation and magmatic dyke emplacement led to a partial reequilibration of the 40Ar/39Ar system until <1500 Ma. This latter phase of mafic magmatism largely coincides with a hot spot event at the scale of the Gawler Craton and western Laurentia paleocontinent.